Multivariable study on growth of diamond on diamond substrates by microwave plasma chemical vapour deposition. (16th January 2019) - Reshi, Bilal Ahmad; Kumar, Shyam; Misra, Anuradha; Varma, Raghava
Abstract: Substrate temperature and methane concentration in Hydrogen (H2 ) gas mixture is the main source for increasing the growth rate, nucleation and grain size of a synthetic diamond. The downside of such an approach is reduced quality. By increasing the chamber pressure, although the quality can be improved, however, it leads to a decrease in the crystal growth rate. Thin diamond films were deposited under hydrogen (H2 ) and methane (CH4 ) gas mixture using microwave plasma chemical vapor deposition (MPCVD) technique. The effect of methane concentration (1%–5%), growth temperature, and pressure on the nucleation of diamond thin films on diamond substrates was investigated. The growth temperature and pressure were maintained in the range of 925 °C–950 °C and 72–75 Torr, respectively. Single crystal diamond (SCD) thin films have been prepared on diamond substrates, which play an important role in the application of the diamond detectors. Different dimensions of films were obtained on diamond substrates with different thicknesses such as 209.17 μ m, 401.73 μ m, and 995.03 μ m for the sample with 1%, 2% and 5% of methane concentration respectively. The roughness, as well as growth rate of these films, were also investigated and were found to be 4.23 nm and 5.02 μ h −1, respectively for 5% methane by optimizing the substrate temperature at 950 °C. Different characterization techniques were used to study the structural, morphological, and compositional properties of the deposited diamond films which confirmed the crystallographic order of the developed diamond film on the diamond substrates.